Cymbelloid diatoms from the River Adegoy, Krasnodar Territory, Russia, with a description of a new species Delicatophycus porosus sp. nov. (Cymbellaceae, Bacillariophyta) - Mironov, Andrei; Chudaev, Dmitry; Jüttner, Ingrid (Phytotaxa, 2022)
This is a taxonomic study of cymbelloid diatoms from the River Adegoy (Krasnodar Territory, Russia). During the survey 24 taxa were recorded including a new species of Delicatophycus. The morphology of Delicatophycus porosus sp. nov. was examined using light and scanning electron microscopy and compared to nine similar species. The new species can be distinguished from similar taxa by a combination of characters: dorsiventral valves with radiate to parallel striae, broadly rounded apices and apical pore fields. Other species found belong to the genera Cymbella, Cymbopleura, Encyonema, Encyonopsis and Reimeria.